Occurrences and field identities of fruit flies in sweet orange (Citrus sinensis) orchards in Sindhuli, Nepal - Adhikari, Debraj; Joshi, Samundra Lal (Journal of Natural History Museum, 2018)
Protocol based fruit fly surveillance made in 2014-15 in citrus orchards in Sindhuli district revealed six species of Bactrocera flies, namely Bactrocera minax (Enderlein), B. cucurbitaeCoquillett, B. dorsalis (Hendel), B. zonata (Saunders), B. tau Walker and B. scutellaris (Bezzi),and one species of Dacus longicornis Weidman. Except B. minax, other fruit flies we recollected in male lure traps, while B. minax fruit flies were also reared to adults from infested sweet oranges. Each species of fruit flies has been morphologically identified up to species level for field identification purpose. D. longicornis is reported for the first time from Nepal.